ENGLISH- MEASURING THE IMPACT OF ISLAMIC MICROFINANCE PRODUCT,QARZ-E-HASNA, ON POVERTY ALLEVIATION IN HYDERABAD DISTRICT - Abdul Ghafoor Ansari; Muhammad Saleh Ansari; Basheer Ahmed Dars (دی اسکالر, 2019)
The objective of this study is to analyze the impact of Islamic microfinance product “Qarz-e-Hasna”provide byan Islamic philanthropic organization Akhuwat on the poverty alleviation of its beneficiaries. The study uses primary data collected through personally structured questionnaire on the randomly selected sample of 120out of the population of 1196beneficiaries of Akhuwat Hyderabad branch. The study found that majority of the beneficiaries were Muslim women within the age groups of 21 to 40 years have obtained the loan of Rs.20,000 each and utilized it for the purpose to expanding their small businesses. The results indicates that Qarz-e-Hasna has improved the living standard of the beneficiaries on accounts of income, expenditure, saving, educational level, households and business assets. Majority of the beneficiaries are satisfied with the terms of loan and the services of Akhuwat.